2012
DOI: 10.1177/0363546511434287
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Passive Motion Exercise Necessary After Arthroscopic Rotator Cuff Repair?

Abstract: Early passive motion exercise after arthroscopic cuff repair did not guarantee early gain of ROM or pain relief but also did not negatively affect cuff healing. We suggest that early passive motion exercise is not mandatory after arthroscopic repair of small to medium-sized full-thickness rotator cuff tears, and postoperative rehabilitation can be modified to ensure patient compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
153
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 19 publications
1
153
2
4
Order By: Relevance
“…They found no difference, however, in longterm functional outcomes between the two groups [62] . In contrast, Kim et al [61] evaluated early and delayed range of motion protocols after rotator cuff repair and found no statistically significant difference in healing rates between the two groups with a trend toward lower re-tear rates in the early range of motion group (12% vs 18%).…”
Section: Rehabilitationmentioning
confidence: 95%
See 1 more Smart Citation
“…They found no difference, however, in longterm functional outcomes between the two groups [62] . In contrast, Kim et al [61] evaluated early and delayed range of motion protocols after rotator cuff repair and found no statistically significant difference in healing rates between the two groups with a trend toward lower re-tear rates in the early range of motion group (12% vs 18%).…”
Section: Rehabilitationmentioning
confidence: 95%
“…Data are conflicting on which, if any, of these programs provides superior results. Early aggressive rehabilitation programs have been shown to result in better early outcomes, pain relief, and range of motion however most studies show no difference with regard to these parameters with longer-term followup [60][61][62][63][64][65][66] . One concern with early aggressive rehabilitation programs is that they may be associated with a higher incidence of tendon re-tear.…”
Section: Rehabilitationmentioning
confidence: 99%
“…Rehabilitation following surgical repair can involve significant periods of time, with some protocols providing guidance to therapists for 4 to 6 months, but this can be extended by complications such as tendon non-healing, which varies from 12% to 94% (Boileau et al, 2005;Galatz, Ball, Teefey, Middleton, & Yamaguchi, 2004;Kim et al, 2012;Thigpen et al, 2016). Tendon healing can be affected by various surgical, mechanical and patient specific factors following surgical repair (Mall, Tanaka, Choi, & Paletta, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to our study, they reported no differences between the different starting periods on the rate of retear or on the range of motion. However, it is important to note that we have excluded, unlike Kim et al, 30) small-sized tears because the rate of retear is generally low in this category. Thus, our study of the repair of rotator cuffs with medium-size or above tears, indicates that delayed passive exercise may reduce the rate of retear.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, Brislin et al 16) reports a rate of stiffness at 8.6% (23 out of 268 patients) after the arthroscopic repair of the rotator cuff. In a study of a similar context, Kim et al 30) investigated the starting period of passive exercise in the repair of rotator cuffs with small-and mediumsized tears. In contrast to our study, they reported no differences between the different starting periods on the rate of retear or on the range of motion.…”
Section: Discussionmentioning
confidence: 99%